Characterization of carboxylated cellulose nanofibrils and oligosaccharides from Kraft pulp fibers and their potential elicitor effect on the gene expression of Capsicum annuum - Cano, María Emilia (2024)
Biomass-derived oligo- and polysaccharides may act as elicitors, i.e., bioactive molecules that trigger plant immune responses. This is particularly important to increase the resistance of plants to abiotic and biotic stresses. In this study, cellulose nanofibrils (CNF) gels were obtained by TEMPO-mediated oxidation of unbleached and bleached kraft pulps. The molecular structures were characterized with ESI and MALDI MS. Analysis of the fine sequences was achieved by MS and MS/MS of the water-soluble oligosaccharides obtained by acid hydrolysis of the CNF gels. The analysis revealed the presence of two families: one corresponding to homoglucuronic acid sequences and the other composed by alternating glucose and glucuronic acid units. The CNF gels, alone or with the addition of the water-soluble oligosaccharides, were tested on Chili pepper (Capsicum annuum). Based on the characterization of the gene expression with Next Generation Sequencing (NGS) of the C. annuum´s total messenger RNA, the differences in growth of the C. annuum seeds correlated well with the downregulation of the pathways regulating photosynthesis. A downregulation of the response to abiotic factors was detected, suggesting that these gels would improve the resistance of the C. annuum plants to abiotic stress due to, e.g., water deprivation and cold temperatures.